COVID-19 and cardiovascular diseases - I. E. Chazova (Терапевтический архив, 2020)
First cases of new coronavirus infection were registered in December 2019. The COVID-19 outbreak was declared a global pandemic. COVID-19 is much more dangerous for people older than 65. It is well known that cardiovascular diseases are more affecting older patients as well. The potentially dangerous combination of the new infection and different cardiovascular diseases has become a crucial problem of cardiology in 2020.